The Effects of International Trade on Wages in Developed and Developing Countries - Wu, Wei (Université d'Ottawa | University of Ottawa, 2005)
In this paper, I provide theoretical and empirical views on how international trade affects wages in developed and developing countries. Following traditional trade theorems, trading with developing countries will hurt low-skilled workers in developed cou